Why did Henry Dunster Reject Infant Baptism?: Circumcision and the Covenant of Grace in the Seventeenth-Century Transatlantic Reformed Community - Macfarlane, Kirsten (The journal of ecclesiastical history, 2021)
In 1653 Henry Dunster, Harvard's first President, refused to baptise his fourth child, initiating a controversy that would end in his resignation from the Harvard presidency in October 1654. This article offers an explanation for Dunster's rejection of infant baptism by re-examining the causes behind the spread of antipaedobaptism across 1640s England and New England, attributing special significance to the Anglophone reception of continental European covenant theology. Supporting this account, it presents an annotated edition of a previously unknown item in Dunster's correspondence, a letter sent to him by a concerned onlooker just months after his heterodoxy became public.